Material choice to optimise the performance index of isogrid structures (Fracture and Structural Integrity, 2023)
Three key qualities should define the structures used in the aviation industry: they should be light, rigid, and strong. These goals can be met by selecting lightweight, high-performance materials like titanium alloy or composites, but careful structural design is also crucial to improve mechanical performance. The structures known as isogrids, which consist of a skin reinforced by a lattice frame, offer an effective way to meet the aforementioned specifications. The structural performances of isogrid-stiffened cylinders composed of various materials were compared in the current work. The structures under investigation were composed of titanium alloy, carbon fibre composite material, or a combination of both. A FEM model was proposed and validated by comparison with experimental results obtained from a composite material structure, and then it was used to simulate the behaviour of all the other structures. While there was some variation in the strength of the parts, it was discovered that the stiffness was almost uniform throughout all of the structures that were examined. But when the weight of the various constructions was taken into account, some very intriguing findings emerged: the composite material-only structure proved to be the most effective because it had the highest specific performances.
Keywords: Carbon fibre; Titanium; Performance index; Finite element analysis; isogrid